Implementation of Clinical Supervision by the Head of Madrasah in Improving Teacher Performance at MTs Badrussalam Kademangan Pagelaran Malang (Qualitative Descriptive Study at MTs Badrussalam Indonesia) - Adyaksa; Rizky Ardian Khoirul Putera; Indah Aminatuz Zuhriyah; Baharuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to describe the planning of clinical supervision programme, clinical stages, and supporting and inhibiting factors for the implementation of clinical supervision at MTs Badrussalam Indonesia. implementation of clinical supervision at MTs Badrussalam Indonesia in Malang City. The method used is a qualitative method with data obtained through interviews, observation, and documentation. The data analysis technique uses an interactive model, including: data collection data reduction, data presentation, and conclusions. The results showed (1) The implementation of the principal's clinical supervision begins with planning the clinical supervision programme and making a schedule for implementing clinical supervision. (2) The implementation of clinical supervision is carried out with the planning stage, the classroom observation stage, the meeting stage (discussion back). (3) Supporting factors for the implementation of clinical supervision: a) The desire to improve the teaching ability of teachers, b) Teachers and staff have expectations to become professional teachers in their fields. The inhibiting factors are: a) the agreed supervision schedule can change, b) teachers who will be supervised often feel tense, c) sometimes there are also technical obstacles such as the use of problematic teaching aids.